2018
DOI: 10.1002/batt.201800052
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Energy for Charging Li‐Ion Batteries Determined by First‐Principles Calculations

Abstract: Charging methods that were employed earlier provided constant energy to a battery, but the negative impact was the activation of chemical reactions that lead to battery passivation. Thus, in order to mitigate the battery aging, moderate energy for charging a lithium‐ion battery has been theoretically calculated using density functional theory. The charging process was associated with a Li‐ion transfer model between two electrodes. When charging, Li‐ions from the positive electrode, pass through a separator/ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Thec harge-transfer resistance (R ct )d ecreased to 73.88 W for 4d,t hus demonstrating faster charge-transfer kinetics and electrical responses. [31] Theother 16 Li ions could be inserted by the electrochemical reaction at the unsaturated carbon atoms of the C5/C6 rings (Figure 2f). [30] Thestructure after lithiation of Te in 4d (see Figure S22) was verified by aDFT calculation; the DG value indicated that the lithium-ion-insertion of Te was as pontaneous reaction.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Thec harge-transfer resistance (R ct )d ecreased to 73.88 W for 4d,t hus demonstrating faster charge-transfer kinetics and electrical responses. [31] Theother 16 Li ions could be inserted by the electrochemical reaction at the unsaturated carbon atoms of the C5/C6 rings (Figure 2f). [30] Thestructure after lithiation of Te in 4d (see Figure S22) was verified by aDFT calculation; the DG value indicated that the lithium-ion-insertion of Te was as pontaneous reaction.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…A study concluded that pulse charging can increase the battery charge capacity, reduce resistance, and thus delay the aging process. The charging voltage for the applied sinusoidal waveform charging strategy was determined 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 according to a previous study, [9] and the charging strategy involves positive and negative voltages. Sinusoidal charging improved the charging time, charging efficiency, maximum rising temperature, and lifetime of the battery.…”
Section: Reviving Aged Lithium-ion Batteries and Prolonging Their Cycmentioning
confidence: 99%
“…Sinusoidal charging improved the charging time, charging efficiency, maximum rising temperature, and lifetime of the battery. [10,11] Thus, DFT calculations suggested the amplitude of the positive voltage to be 0.7 V. [9] The negative voltage step was designed to reverse SEI formation. Most experiments have been done without physiochemical aspects.…”
Section: Reviving Aged Lithium-ion Batteries and Prolonging Their Cycmentioning
confidence: 99%
See 2 more Smart Citations